Diversity of marine bryozoans inhabiting demosponges in northeastern Brazil - Almeida, Ana C.s.; Souza, Facelucia B.c.; Menegola, Carla; Vieira, Leandro M. (Zootaxa, 2017)
As primary or obligate sessile organisms, bryozoans depend upon a substratum resource that affects their abundance, distribution and diversity. These animals can colonize virtually any type of substratum, including other organisms and artificial structures. Associations between bryozoans and sponges are commonly reported in the literature, but there are few studies discussing the association between these two taxa in detail. Here we present data on the bryozoan community found on shallow-water sponges from Bahia coast, northeastern Brazil, including their taxonomic status, colony form and adaptative structures utilized by these bryozoans to grow on sponges. Twenty-one bryozoan species were found attached to the surface of sixteen species of sponges. Five new species of cheilostome bryozoans are described. A total of 105 colonies were studied and most of them are erect delicate branching (44 colonies) and encrusting patches (34 colonies). The majority of bryozoan colonies were attached to the surface of rugose-textured sponges (67 colonies; 61%). This suggests that bryozoans are more likely to settle on irregular and rough surfaces. Patches colonies were mainly attached to the portion of the sponge that was in contact with the seabed, and spot colonies were particularly found in spatial refuges, showing the preference of larvae to settle on shaded and less exposed substrata. Most erect bryozoans were attached to the lateral sponge surface, other colonies grew on the underside and few on the upper surface of the sponges. These colonies were attached either using anchoring rhizoids, rigid bases, or stolons. The bryozoan species and genera reported here are common in northeastern Brazil and considered generalists in terms of larval settlement requirements. The bryozoan-sponge association studied is considered a non-obligatory commensalism (inquilinism).